The impact of pronouns on the reception of supernatural creatures in Sapkowski’s short stories - Michalina Piotrowska (Językoznawstwo)
This paper seeks to analyse two translations of Andrzej Sapkowski’s books Ostatnie życzenie (The Last Wish) and Miecz przeznaczenia (Sword of Destiny) with the focus on pronouns used by the author and translators (Danusia Stok and David French) in relation to the supernatural creatures presented in the short stories. The text deals with the impact these pronouns can have on the perception of such creatures.